Metaverse: Technological evolution and social impact - Marković-Blagojević Marija; Radić Nikola; Cvjetković Milena (Trendovi u Poslovanju)
The Metaverse represents a new phase of technological development, integrating virtual reality, augmented reality, blockchain, and artificial intelligence to create immersive digital environments. This paper explores the historical context, technical foundations, and social implications of the Metaverse. Through the evolution of virtual worlds and technological advancements, the Metaverse is becoming increasingly prevalent, offering richer socialization experiences and economic opportunities while simultaneously raising concerns about privacy, security, and media addiction. National policies and the attitudes of international organizations also play a crucial role in shaping the future of the Metaverse, with different countries having different strategies and priorities. The paper examines theoretical perspectives and future research directions, along with recommendations for responsible management of the Metaverse. Proper regulation and design can ensure that the potential of the Metaverse enriches human experience while safeguarding social well-being.